PERLINDUNGAN HAK MASYARAKAT HUKUM ADAT DALAM PEMANFAATAN DAN PENGELOLAAN HUTAN PERSPEKTIF HAK ASASI MANUSIA DI BIDANG EKONOMI SOSIAL DAN BUDAYA - Riswanda ramadhan (TADULAKO MASTER LAW JOURNAL, 2024)
The purpose of this paper is to analyze: 1) Protection of customary law communities' rights in forest utilization and management. 2) The perspective of human rights in the economic, social and cultural fields related to forest management by indigenous peoples. The writing method used is normative legal research or library legal research using a statutory approach, case approach, and conceptual approach. The results of the research show that: 1) Protection of the rights of indigenous peoples in the utilization and management of forests by providing prior recognition to indigenous peoples through Regional Regulations, after the existence of indigenous peoples is recognized, the status of customary forests is determined by the Minister of Environment and Forestry, both of which are conditions for indigenous peoples to get protection for the utilization and management of their customary forests. Forest management carried out by indigenous peoples based on their local wisdom is utilized to meet their daily needs and community needs. 2) In the perspective of human rights, the rights of indigenous peoples are respected and protected in the context of protecting and upholding human rights as long as they do not conflict with the principles of the rule of law which is based on justice and the welfare of the people, one of the recognized rights of indigenous peoples is the right to manage their customary forests to fulfill their daily needs and their communities. In the International Covenant on Economic, Social and Cultural Rights, which has been ratified into Law No. 11/2005, the most essential right of indigenous peoples is the right to land and natural resources.